Triterpenoid saponins from the roots of Acanthophyllum gypsophiloides Regel - Khatuntseva, Elena A.; Men’shov, Vladimir M.; Shashkov, Alexander S.; Tsvetkov, Yury E.; Stepanenko, Rodion N.; Vlasenko, Raymonda Ya.; Shults, Elvira E.; Tolstikov, Genrikh A.; Tolstikova, Tatjana G.; Baev, Dimitri S.; Kaledin, Vasiliy A.; Popova, Nelli A.; et al. (Beilstein Journal of Organic Chemistry, 2012)
Two new triterpenoid saponins 1 and 2 were isolated from the methanol extract of the roots of Acanthophyllum gypsophiloides Regel. These saponins have quillaic acid or gypsogenin moieties as an aglycon, and both bear similar sets of two oligosaccharide chains, which are 3-O-linked to the triterpenoid part trisaccharide α-L-Arap-(1→3)-[α-D-Galp-(1→2)]-β-D-GlcpA and pentasaccharide β-D-Xylp-(1→3)-β-D-Xylp-(1→3)-α-L-Rhap-(1→2)-[β-D-Quip-(1→4)]-β-D-Fucp connected through an ester linkage to C-28. The structures of the obtained saponins were elucidated by a combination of mass spectrometry and 2D NMR spectroscopy. A study of acute toxicity, hemolytic, anti-inflammatory, immunoadjuvant and antifungal activity was carried out. Both saponins 1 and 2 were shown to exhibit immunoadjuvant properties within the vaccine composition with keyhole limpet hemocyanin-based immunogen. The availability of saponins 1 and 2 as individual pure compounds from the extract of the roots of A. gypsophiloides makes it a prospective source of immunoactive agents.
Keywords: Acanthophyllum gypsophiloides; adjuvant; hemolysis; NMR; saponin; structure